Analisis Profil Keterampilan Sosial pada Peserta Didik Sekolah Dasar - Alya Rahma Audia; Supianto Supianto (Jurnal Pendidikan Dasar, 2025)
This study aims to describe the social skills profile of elementary school students. The method used in this research is quantitative descriptive. The subjects of this study were 231 Phase C students in grades 5 and 6. There were three elementary schools in Banjarsari District used in this study. The results of all students showed that the excellent category was 12%, the good category was 43%, the fair category was 28%, and the poor category was 17%. It can be concluded that the profile of social skills in elementary school students is good.